THE ROLE OF PEDAGOGICAL CONTENT KNOWLEDGE IN IMPROVING ELEMENTARY TEACHER' TEACHING EFFECTIVENESS - R.Taufiq Nur Muftiyanto; Oktiana Handini (Adisam Publisher, 2026)
This study aims to examine the role of Pedagogical Content Knowledge in enhancing the effectiveness of elementary school teachers' instruction thru a literature review approach. The background of the research is based on the importance of teachers' professional competence in facing the demands of 21st-century learning, which emphasizes conceptual understanding, active engagement, and meaningful learning. The method used is qualitative research by reviewing various scientific sources in the form of national and international journal articles, educational books, conference proceedings, as well as relevant theses and dissertations. The study results indicate that Pedagogical Content Knowledge plays a significant role in improving the quality of learning thru the presentation of more concrete concepts, the ability to address student misconceptions, and the enhancement of two-way interaction in the classroom. Teachers with a high level of Pedagogical Content Knowledge are able to design learning strategies that align with the characteristics of elementary school students, thereby encouraging active engagement and deeper conceptual understanding. Moreover, Pedagogical Content Knowledge contributes to the improvement of students' learning outcomes and critical thinking skills because the learning process focuses on understanding rather than mere memorization. This study concludes that strengthening Pedagogical Content Knowledge is a key factor in enhancing the effectiveness of elementary school teachers' instruction. Therefore, the professional development of teachers needs to be directed toward training based on Pedagogical Content Knowledge so that the quality of learning in elementary schools improves sustainably.